2010
DOI: 10.1186/1742-6405-7-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking on lung function, respiratory symptoms and respiratory diseases amongst HIV-positive subjects: a cross-sectional study

Abstract: BackgroundSmoking prevalence in human immunodeficiency virus (HIV) positive subjects is about three times of that in the general population. However, whether the extremely high smoking prevalence in HIV-positive subjects affects their lung function is unclear, particularly whether smoking decreases lung function more in HIV-positive subjects, compared to the general population. We conducted this study to determine the association between smoking and lung function, respiratory symptoms and diseases amongst HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 30 publications
(40 reference statements)
3
51
3
Order By: Relevance
“…Moreover, several studies on the association of COPD and HIV did not take into consideration pulmonary tuberculosis. Instead, most of these studies found pneumonia to be an independent factor associated with COPD [4,6,7]. We found no relationship between history of pneumonia and COPD.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Moreover, several studies on the association of COPD and HIV did not take into consideration pulmonary tuberculosis. Instead, most of these studies found pneumonia to be an independent factor associated with COPD [4,6,7]. We found no relationship between history of pneumonia and COPD.…”
Section: Discussioncontrasting
confidence: 50%
“…Failure in some previous studies to demonstrate any significant effect of past pulmonary tuberculosis on the occurrence of COPD among HIV subjects was probably due to the lack of statistical power. For instance, in the study conducted by Crothers and al only 8 (7%) patients out of 104 HIV-positive patients had a history of tuberculosis [5] while only 5 (4%) out of 119 HIV patients had tuberculosis in the study by Cui et al [4]. Moreover, several studies on the association of COPD and HIV did not take into consideration pulmonary tuberculosis.…”
Section: Discussionmentioning
confidence: 95%
“…The association of ART and airway obstruction persisted even after adjustment for other risk factors, such as age and smoking history. Another study of 119 HIV-infected participants also performed spirometry and found that 3.4% had airway obstruction (14). Lung function was worse in smokers, and over half of the participants reported respiratory symptoms.…”
Section: Epidemiology Of Hiv and Copd In The Antiretroviral Eramentioning
confidence: 99%
“…There have been three recent prospective studies that examined respiratory symptoms and measured pulmonary function in the era of combination ART (13)(14)(15). The first study performed spirometry in 234 HIV-infected outpatients without a history of acute respiratory disease or asthma (13).…”
Section: Epidemiology Of Hiv and Copd In The Antiretroviral Eramentioning
confidence: 99%
“…In the Veterans Aging Cohort Study, a predominantly smoking older male cohort, asthma diagnosis was similar between individuals with and those without HIV (41). Two recent studies with a broader population of individuals with HIV have found that 11 and 21%, respectively, have an asthma diagnosis by history (doctor-diagnosed asthma) (46,47). These prevalence estimates may be greater than the estimated prevalence of approximately 7.6% in the general population (48).…”
Section: Obstructive Lung Disease: Associations With Hivmentioning
confidence: 55%